Operational Analysis of Power Generation from a Photovoltaic–Wind Mix and Low-Emission Hydrogen Production - Arkadiusz Małek; Andrzej Marciniak (Energies)
Low-emission hydrogen generation systems require large amounts of energy from renewable energy sources. This article characterizes the production of low-emission hydrogen, emphasizing its scale and the necessity for its continuity. For hydrogen production defined in this way, it is possible to select the appropriate renewable energy sources. The research part of the article presents a case study of the continuous production of large amounts of hydrogen. Daily production capacities correspond to the demand for the production of industrial chemicals and artificial fertilizers or for fueling a fleet of hydrogen buses. The production was placed in the Lublin region in Poland, where there is a large demand for low-emission hydrogen and where there are favorable conditions for the production of energy from a photovoltaic–wind mix. Statistical and probabilistic analyses were performed related to the generation of power by a photovoltaic system with a peak power of 3.45 MWp and a wind turbine with an identical maximum power. The conducted research confirmed the complementarity and substitutability relationship between one source and another within the energy mix. Then, unsupervised clustering was applied using the k-Means algorithm to divide the state space generated in the power mix. The clustering results were used to perform an operational analysis of the low-emission hydrogen generation system from a renewable energy sources mix. In the analyzed month of April, 25% of the energy generated in the photovoltaic–wind mix came from the photovoltaic system. The low-emission hydrogen generation process was in states (clusters), ensuring that the operation of the electrolyzer with nominal power amounted to 57% of the total operating time in that month. In May, the share of photovoltaics in the generated power was 45%. The low-emission hydrogen generation process was in states, ensuring that the operation of the electrolyzer with nominal power amounted to 43% of the total time in that month. In the remaining states of the hydrogen generation process, the power must be drawn from the energy storage system. The cluster analysis also showed the functioning of the operating states of the power generation process from the mix, which ensures the charging of the energy storage. The conducted research and analyses can be employed in planning and implementing effective climate and energy transformations in large companies using low-emission hydrogen.